2007
DOI: 10.1021/jm061361d
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Substituted Resorcinol Hydrophobicity Augments Tyrosinase Inhibition Potency

Abstract: The objective of the present study was to investigate to what extent the addition of hydrophobic residues to a 2,4-resorcinol derivative would contribute to their tyrosinase inhibitory potency. Hence, 3-(2,4-dihydroxyphenyl)propionic acid, isolated from Ficus carica, was transformed into esters, and the relationship between the structure of these esters to their mushroom tyrosinase inhibition activity was explored. The enzyme crystallographic structure, published recently (Matoba, Y. et al. J. Biol. Chem. 2006… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
37
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 25 publications
2
37
0
Order By: Relevance
“…Introducing a methyl group into position 5 of resorcinol to yield orcinol led to a slight decrease in inhibition (50.79%). Khatib et al 10) reported that tyrosinase inhibitors containing a resorcinol subunit are typically highly active, and 2,4-resorcinol derivatives are significantly more potent than 3,5-substituted counterparts. Introduction of a carboxyl into position 4 of orcinol to produce orsellinic acid slightly diminished diphenolase inhibition to 63.35% an inhibitory level still higher than that of 82.69% observed for lecanoric acid.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Introducing a methyl group into position 5 of resorcinol to yield orcinol led to a slight decrease in inhibition (50.79%). Khatib et al 10) reported that tyrosinase inhibitors containing a resorcinol subunit are typically highly active, and 2,4-resorcinol derivatives are significantly more potent than 3,5-substituted counterparts. Introduction of a carboxyl into position 4 of orcinol to produce orsellinic acid slightly diminished diphenolase inhibition to 63.35% an inhibitory level still higher than that of 82.69% observed for lecanoric acid.…”
Section: Resultsmentioning
confidence: 99%
“…Khatib et al 10) suggested that the increasing inhibitory potency exhibited by 3-(2,4-dihydroxyphenyl) propionic esters does not necessarily correlate with longer alkyl chains, but may be related to the increasing volume of ester groups. Similar results were obtained by Kubo et al 4) for esters of gallic acid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3) However, recently studies showed that the abnormal accumulation of pigmentation causes the quality loss of vegetables and fruits and various dermatological disorders, such as hyperpigmentation, freckles, melasma, ephelide, and senile lentigines. 4) Furthermore, the melanin pigments are also found in the mammalian brain where tyrosinase plays a key role in the synthesis of neuromelanin and is linked to Parkinson's and other neurodegenerative diseases. 4,5) Therefore, tyrosinase inhibitors should be clinically useful for the treatment of some dermatological disorders associated with melanin hyperpigmentation and also important in cosmetics and food industry.…”
mentioning
confidence: 99%
“…4) Furthermore, the melanin pigments are also found in the mammalian brain where tyrosinase plays a key role in the synthesis of neuromelanin and is linked to Parkinson's and other neurodegenerative diseases. 4,5) Therefore, tyrosinase inhibitors should be clinically useful for the treatment of some dermatological disorders associated with melanin hyperpigmentation and also important in cosmetics and food industry. [6][7][8] So far, a large number of potential tyrosinase inhibitors have been described from natural source, such as kojic acid (Fig.…”
mentioning
confidence: 99%